5(4H)-Oxazolones as Effective Aminoacylation Reagents for the 3′-Terminus of RNA - Liu, Ziwei; Hanson, Cassandra; Ajram, Ghinwa; Boiteau, Laurent; Rossi, Jean-Christophe; Danger, Grégoire; Pascal, Robert (Synlett, 2017)
Nucleosides and methylated nucleotide models were used as substrates to identify pathways for the chemical aminoacylation of ribonucleic acids (RNA) as a prerequisite for the evolution of translation. A selective and comparatively efficient reaction of a 5(4H)-oxazolone with the 2′- and 3′-OH of the ribonucleotide models was observed. Surprisingly, a similar reaction starting from an α-amino acid N-carboxyanhydride (NCA), selected as an acylating agent potentially leading to the unprotected ester required for translation, was not observed, which was confirmed using an acylated NCA equivalent. The reasons for this difference are analysed.
Keywords: origin of translation; prebiotic chemistry; peptides; nucleotides; co-evolution